Multi‐methodological Geophysical Exploration for the Interpretation of the Ancient Landscape of Phaistos (Greece). Issue 4 (19th July 2016) - Di Maio, Rosa; La Manna, Mauro; Piegari, Ester; Mancini, Cecilia; Achilli, Vladimiro; Fabris, Massimo
Abstract: Phaistos is one of the main Minoan palatial sites in the Aegean context. The ancient sources and the scarce archaeological records indicate that the city, destroyed by the nearby town of Gorthina during second centurybc, underwent also an important post‐palatine phase from alto‐archaic and archaic age to Hellenistic age, still scarcely excavated. Thus, in recent years, new research that integrate different methodologies has been performed to study part of the western Mesara plain, with a special focus on the area around the Phaistos' hills and the underlying plateau. In this paper, the results of high‐resolution magnetic, electromagnetic, electrical and aerial photogrammetric surveys carried out in an area south of Phaistos site (Haghios Ioannis) are reported. All geophysical and geomatic data are consistent in showing a sharp contrast in soil properties of the northern and southern sectors of the survey area, which could help the paleoenvironmental reconstruction of the large lake developed at the foot of the Phaistos hill during the Minoan age. Furthermore, several deep and shallow anomalies with regular geometric shapes suggest the presence of different types of buried structures. In particular, in the shallowest part of the subsoil, all observed data show elongated structures, whose geometry and physical properties well correlate with the presence of wall remains, and an anomaly feature with a semicircular shape also detected by previous orthophoto interpretation studies. Copyright © 2016 John Wiley & Sons, Ltd.